Influence of redmud on the mechanical, damping and chemical resistance properties of banana/polyester hybrid composites - Arumuga prabu, V.; Uthayakumar, M.; Manikandan, V.; Rajini, N.; Jeyaraj, P. (Materials in engineering, 2014)
•Redmud, an industrial waste has been used for making the composite.•Tensile strength was improved when the particle size of redmud was decreased.•The flexural and impact strength of BFRPCs were influenced by the particle size.•Reduced particle size of the redmud produced highest modal damping on the BFRPCs. A novel hybrid composite was developed with the addition of redmud as secondary reinforcing filler with banana fiber reinforced polyester composites (BFRPCs). The effect of varying parameters such as particle size (4, 6 and 13μm) and weight percentage (2, 4, 6, 8 and 10wt%) of redmud were analyzed on static mechanical, free vibration and chemical resistance properties of hybrid composites. The addition of redmud shown enhanced performance compared to the virgin BFRPCs in all the above said properties. The maximum increase of 50% in mechanical strength was observed for the BFRPCs with the addition of redmud having 4μm particle size and 8wt% of filler content compared to pure BFRPCs. The increased value of fundamental natural frequencies with associated modal damping characteristics of redmud filled BFRPCs were found using half-power band width method. All the fabricated composites performed well against various chemicals and it indicates that the resistance to the weight loss is due to the uniformly distributed redmud. To study the effect of redmud on interfacial bonding between the banana fiber and polyester matrix the Scanning Electron Microscope (SEM) image analysis was performed.